Managing uncertainty in soil carbon feedbacks to climate change - Bradford, Mark A.; Wieder, William R.; Bonan, Gordon B.; Fierer, Noah; Raymond, Peter A.; Crowther, Thomas W. (Nature climate change, 2016)
Planetary warming may be exacerbated if it accelerates loss of soil carbon to the atmosphere. This carbon-cycle–climate feedback is included in climate projections. Yet, despite ancillary data supporting a positive feedback, there is limited evidence for soil carbon loss under warming. The low confidence engendered in feedback projections is reduced further by the common representation in models of an outdated knowledge of soil carbon turnover. 'Model-knowledge integration' — representing in models an advanced understanding of soil carbon stabilization — is the first step to build confidence. This will inform experiments that further increase confidence by resolving competing mechanisms that most influence projected soil-carbon stocks. Improving feedback projections is an imperative for establishing greenhouse gas emission targets that limit climate change. Climate change may accelerate decomposition of soil carbon leading to a reinforcing cycle of further warming and soil carbon loss. This Review considers the uncertainties and modelling challenges involved in projecting soil responses to warming.